Escravos e libertos nos serviços domésticos no Recife no Século XIX: mudanças e continuidades - Lima, Tatiana Silva de (2021)
This thesis emphasizes on the slaves and freedmen experience in domestic services in Recife between 1830 and 1888. It investigates how the conjunctures arising from the laws that gradually and slowly emancipated the captives and developed the world of free labor had repercussions on the relations of these subjects in domestic work. From the laborious relationship between qualitative and quantitative methods, post-mortem inventories were analyzed (their lists of description and valuation of assets, their wills, manumission letters and other supporting documents of manumission, decisions of the Orphans Court, petitions and payment receipts of unpaid wages), periodicals, literature, travel literature, population censuses, dictionaries of the time, public conferences, petitions from private schools, police documentation and Postures Regulation all free status of person (created to serve). The interpretations of the documentation underlying the hypothesis that domestic slaves and freedmen have always had difficulties to get favorable conditions of work, even more than the exploited in other occupations, however, it has worsened in the last two decades of slavery. This is because the slave relations, paternalistic and domesticity were very strong in Recife, infiltrating significantly in relations of domestic work. So much so that captives were more exploited in domestic services than in other activities, despite the increasing decrease in the proportion of them in the population, and the average number of domestic (especially slaves) in families remained expressive and stable throughout the chronological cut, from 1830 to 1888. Moreover, domestic liners continued longer limited to the domain of the former masters in post-emancipation, conditioned to provide services for granted and obligations imposed, far from laws designed to develop the world of free labor. Only, at times, freed and free maids and nannies approached freedom of work, reaching contractual relations and wages, but almost always marked by domesticity, precariousness and dependence. Domestic workers claimed, negotiated and resisted to reduce and even end exploitation on them and to achieve better working conditions. But, starting from the conjuncture around 1871, when the crisis of slavery worsened, reaching the statutory and employer authority, and the free occupied most of the domestic service posts, the dominant ones certainly erected more obstacles for the domestic workers obtain rights and thus retain their privileges.